Fluctuation of annexin-A1 positive mast cells in chronic granulomatous inflammation - Oliani, S. M. [UNESP]; Ciocca, G. A. Panin [UNESP]; Pimentel, T. A.; Damazo, A. S. [UNESP]; Gibbs, L.; Perretti, M. (Birkhauser Verlag Ag, 2008)
Objective: We have applied here a model of chronic granulomatous inflammation to study the profile of mast cell activation and their expression of annexin-A1 in the nodular lesion.Materials: Granulomatous inflammation was induced by injection of croton oil and Freund's complete adjuvant (CO/FCA) into the dorsal air-pouches of mice. Skin tissue samples were collected from control group (24 h time-point; i.e. before disease development) and 7, 14, 21, 28 and 42 days post-CO/FCA treatment.Results: Histopathological analyses revealed an on-going inflammation characterized by an increased number of activated mast cells at sites of the chronic inflammatory reaction in all experimental groups. Immunohistochemical analysis showed skin mast cells highly immunoreactive for annexin-A1, both at an initial (day 7) and a delayed (day 28) phase of the inflammatory reaction.Conclusions: The observed time-dependent modulation of mast cell activation, during the granulomatous injury, indicates that multiple pathways centred on annexin-A1 might become activated at different stages of this chronic inflammatory response, including the delayed and pro-resolving phase.
Keywords: Lipocortin 1; Mast cells; Air-pouch model; Skin; Neutrophil; Granuloma